P107 Autoimmune lymphoproliferative syndrome (ALPS) in a child: a new disorder to 'climb'. (6th June 2017) - Manca, E; Petraccaro, A; Gorgoglione, S; Pacilio, A; Maggio, A; Spirito, A; Santis, R De; Miglionico, L; Maruzzi, M; Ciliberti, A; Pianella, V Verrotti di; Ladogana, S; et al.
Abstract : Autoimmune lymphoproliferative syndrome (ALPS) is a rare disorder of the immune system caused by a mutation in the Fas apoptotic pathway. It can present with a wide range of clinical manifestations, including noninfectious nonmalignant lymphoadenopathy, splenomegaly and autoimmune pathology (frequently autoimmune citopenias). Revised diagnostic criteria allowed an improvement in its management. A 3-year-old boy was hospitalised for severe isolated thrombocytopenia (PLT 8000/mcl) and hemorragic syndrome. On physical examination, he had inguinal limphoadenopathy. His blood exams showed positivity for autoimmunity and normal lymphocyte population. Bone marrow aspirate revealed an immune throbocytopenia, so he started treatment with Immunoglobulins (Ig), with a good response. We performed an exeresis of his inguinal lymph node, increasing in dimensions, and found reactive follicular hyperplasia with dermatopathic aspects in absence of neoplasy. After one month, thrombocytopenia associated with neutropenia (N 800/mcl), positivity of direct and indirect Coombs test, anti-neutrophils antibodies negatives and splenomegaly on sonography. He assumed steroids for 2 weeks, with a good response. After 4 months, he presented again with thrombocytopenia, associated with emolitic autoimmune anaemia (Hb 5, 2 g/dl) so he began therapy with Ig and steroids, with initial good response. Two months after stop therapy, new episode of thrombocytopenia, hemorragic syndrome and an increase of his splenomegaly. Therefore, we performed FAS-induced apoptosis test (negative) and researched double negative lymphocites that were positive (CD3+TCRαβ+CD4-CD8-:3, 5%; CD19+CD27+:4, 8%; CD3+CD25+/CD3+HLADR+ ratio:0, 1%). He started therapy with mycophenolate mofetil and with Ig on demand. As we obteined a poor response, we shifted it to syrolimus, with progressive reduction of splenomegaly and increase of PLT. ALPS is a rare pathology that should be investigated in children with autoimmune citopenias and nonmalignant limphoproliferation. Its various clinical manifestations complicate diagnosis and treatment. First line treatment includes prednisone and Ig; for unresponsive patients mycophenolate mofetil and syrolimus are effective, the latter in children with refractory multilineage autoimmune cytopenias. Research over the past decades have increased our knowledge on its pathophysiology resulting in an improvement of its management. Its diagnosis is indeed crucial as ALPS may progress to lymphoma.